Larval morphology of the antlion Myrmecaelurus trigrammus (Pallas, 1771) (Neuroptera, Myrmeleontidae), with notes on larval biology - Devetak, Dušan; Klokočovnik, Vesna; Lipovšek, Saška; Bock, Elisabeth; Leitinger, Gerd (Zootaxa, 2013)
Morphology and behaviour of third instar larvae of the Holomediterranean antlion species Myrmecaelurus trigrammus (Pallas) are described. Larvae are facultative pit-builders, they either ambush their prey at the surface, or dig pitfall traps that prey fall in to. Dark brown spots on dorsal and ventral sides of the head and on dorsal side of the thorax are charac-teristic of the larvae. Eye tubercles are not prominent. Jaws are equipped with long bristles, campaniform sensilla, sensilla coeloconica, and digitiform sensilla. A unique feature is the shape of the tips of all three teeth that is screw-like with a polyhedral surface. The body surface is covered with longitudinally grooved bristles and plumose hairs. On the tip of the antennae and on terminal and subterminal parts of labial palps sensilla basiconica occur. On the 9th abdominal segment there are two bulges, each of them bearing four digging bristles. Non-prominent eye tubercles and numerous mandibular bristles are morphological traits of pit-builders. Most of the behavioural traits are related to pit builders, whereas forward movement, waiting for prey without a pit and frequent changing of ambush location are traits of non-pit builders.